2017
DOI: 10.1371/journal.pntd.0005612
|View full text |Cite
|
Sign up to set email alerts
|

Dose of antivenom for the treatment of snakebite with neurotoxic envenoming: Evidence from a randomised controlled trial in Nepal

Abstract: BackgroundCurrently, there is inadequate evidence on which to base clinical management of neurotoxic snakebite envenoming, especially in the choice of initial antivenom dosage. This randomised controlled trial compared the effectiveness and safety of high versus low initial antivenom dosage in victims of neurotoxic envenoming.Methodology/ Principal findingsThis was a balanced, randomised, double-blind trial that was conducted in three health care centers located in the Terai plains of Nepal. Participants recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 30 publications
0
20
0
1
Order By: Relevance
“… 10 11 12 22 Studies on preclinical efficacy, pharmacokinetics, clinical effectiveness, and safety of current antivenoms are lacking. 37 39 56 61 The optimal dose of antivenom is still debated and regional clinical trials offer conflicting evidence. A systematic review of 10 open label randomised controlled trials in the Indian subcontinent on optimal antivenom dose concluded that there is very low quality evidence to guide practice and further research is needed.…”
Section: Why Do These Problems Persist?mentioning
confidence: 99%
“… 10 11 12 22 Studies on preclinical efficacy, pharmacokinetics, clinical effectiveness, and safety of current antivenoms are lacking. 37 39 56 61 The optimal dose of antivenom is still debated and regional clinical trials offer conflicting evidence. A systematic review of 10 open label randomised controlled trials in the Indian subcontinent on optimal antivenom dose concluded that there is very low quality evidence to guide practice and further research is needed.…”
Section: Why Do These Problems Persist?mentioning
confidence: 99%
“…The objective clinical endpoint used by Alirol et al in neurotoxic envenoming could be adapted as an efficacy endpoint in an adaptive design, i.e. the avoidance of ventilation from a starting position of pre-defined neurological impairment [25]. These simulation studies for both the model based and rule based designs highlight the need for larger phase 2 type dose-finding trials.…”
Section: Discussionmentioning
confidence: 99%
“…those occurring in 5% or fewer patients). In the dose-finding trials displayed in Supplementary Table S1, six studies demonstrate a trend suggestive of a dose-toxicity relationship [24, 25, 3841], two studies show the opposite relationship [42, 43] and the remaining eight studies do not report toxicity as an outcome. An earlier study by Reid with large numbers of patients was suggestive of a dose-toxicity relationship [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The objective clinical endpoint used by Alirol et al in neurotoxic envenoming could be adapted as an efficacy endpoint in an adaptive design, i.e. improvement in FEV1 or the avoidance of ventilation from a starting position of pre-defined neurological impairment [27]. These simulation studies for both the model based and rule based designs highlight the need for larger phase 2 type dose-finding trials.…”
Section: The Importance Of Choosing the Correct Efficacy And Toxicitymentioning
confidence: 99%